PENGARUH PENGGUNAAN SMARTPHONE TERHADAP AKHLAK REMAJA DI ALAHAN ANGGANG JORONG GUMARANG II - Rezka Rahmadani; Junaidi; Iswantir; Arifmiboy (KOLONI, 2022)
The problem in this study is the number of teenagers who do not pray, spend a long time using smartphones, such as accessing social media, playing games and other smartphone applications, indicators of smartphone use, namely frequency, duration and content. The purpose of this study was to find out how much influence the use of smartphones had on adolescent morals in Alahan Anggang Jorong Gumarang II. This study uses a quantitative approach, while the data used are primary data obtained by means of a questionnaire using a Likert scale given to 33 teenagers in Alahan Anggang Jorong Gumarang II, the data analysis techniques in this study are descriptive analysis, normality test, regression test. simple linear. The results showed that there was a variable influence of smartphone use on adolescent morals. Thus Ha is accepted and Ho is rejected. Shows that the proportion of the influence of smartphone use on adolescent morals is 0.304 or 30.4%, while the remaining 69.6% is influenced by other variables that are not in the research that the author did.